Possibility for use essential oils in veterinary medicine and animal husbandry with special emphasis on oregano oil - Vučinić Marijana; Nedeljković-Trailović Jelena; Trailović Saša; Ivanović Saša; Milovanović Mirjana; Krnjaić Dejan (Veterinarski Glasnik, 2012)
The paper reviews the latest studies on possible applications of oregano essential oil in veterinary medicine and animal livestock production. The first part of the paper deals with the definition of essential oils, possibilities for their extraction from plants, possibilities for their application in human and veterinary medicine, the interest of a science in essential oils, and, essential oils classification based on their use in human and veterinary medicine. The second part of the review deals with the properties of oregano essential oil, its main active principles, carvacrol and thymol and its application in veterinary medicine and animal livestock production. Oregano essential oil may be applied in animal feed, in the treatment of coccidiosis of domestic animals and candidiasis. It can be applied as a larvicide, repellent, insecticide and acaricide. It is used in aquaculture to treat fish diseases caused by bacteria and parasites or in the hatchery industry as a disinfectant for eggs or for disinfection of manure. The greatest potential of oregano essential oil is the possibility of its application in organic agriculture and organic animal husbandry. [Projekat Ministarstva nauke Republike Srbije, br. TR 31087]